The Culture of Leadership in Contemporary China : Conflict, Values, and Perspectives for a New Generation - Linehan, Paul Michael (Lexington Books, 2017)
This study examines the culture of leadership-within the government, the Communist Party, and business-in contemporary China. The author analyzes the conflict between traditional Chinese values, communist ideology, and Western liberalism.